can you please solve this problem from trigonometry
Attachments:
![](https://hi-static.z-dn.net/files/dde/1f3d856c6a757e46052895946a47406d.jpg)
Answers
Answered by
1
hey !!!
tan¢ + cot¢ = 2sin²¢ + 2 cos² ¢
=> tan¢ + cot¢ = 2( sin²¢ + cos²¢)
=> tan¢ + cot¢ = 2 ×1 =2 .........1)
_____________________________
tan⁴¢ + cot⁴¢
=>( tan² ¢) ² + (cot² ¢ )²
=> (cot²¢ + cot²¢ )² -2 cot²¢ × tan²¢
=> { ( cot¢ + tan¢ ) ²-2tan¢×cot¢ } -2 cot²¢ × tan²¢
=> (2)² -2 ×1 -2 ×1 { from 1 equation}
=> 4 - 2 -2
=> 4 -4 =0 ...Answer.
hope it helps you !!
#Rajukumar111
tan¢ + cot¢ = 2sin²¢ + 2 cos² ¢
=> tan¢ + cot¢ = 2( sin²¢ + cos²¢)
=> tan¢ + cot¢ = 2 ×1 =2 .........1)
_____________________________
tan⁴¢ + cot⁴¢
=>( tan² ¢) ² + (cot² ¢ )²
=> (cot²¢ + cot²¢ )² -2 cot²¢ × tan²¢
=> { ( cot¢ + tan¢ ) ²-2tan¢×cot¢ } -2 cot²¢ × tan²¢
=> (2)² -2 ×1 -2 ×1 { from 1 equation}
=> 4 - 2 -2
=> 4 -4 =0 ...Answer.
hope it helps you !!
#Rajukumar111
Similar questions